Proteus mirabilis urease: operon fusion and linker insertion analysis of ure gene organization, regulation, and function. - Island, M D (1995)
Urease is an inducible virulence factor of uropathogenic Proteus mirabilis. Although eight contiguous genes necessary for urease activity have been cloned and sequenced, the transcriptional organization and regulation of specific genes within the Proteus gene cluster has not been investigated in detail. The first gene, ureR, is located 400 bp upstream and is oriented in the direction opposite the other seven genes, ureDABCEFG. The structural subunits of urease are encoded by ureABC. Previously, UreR was shown to contain a putative helix-turn-helix DNA-binding motif 30 residues upstream of a consensus sequence which is a signature for the AraC family of positive regulators; this polypeptide is homologous to other DNA-binding regulatory proteins. Nested deletions of ureR linked to either ureD-lacZ or ureA-lacZ operon fusions demonstrated that an intact ureR is required for urea-induced synthesis of LacZ from either ureA or ureD and identified a urea-regulated promoter in the ureR-ureD intergenic region. However, lacZ operon fusions to fragments encompassing putative promoter regions upstream of ureA and ureF demonstrated that no urea-regulated promoters occur upstream of these open reading frames; regions upstream of ureR, ureE, and ureG were not tested. These data suggest that UreR acts as a positive regulator in the presence of urea, activating transcription of urease structural and accessory genes via sequences upstream of ureD. To address the role of the nonstructural regulatory and accessory genes, we constructed deletion, cassette, and linker insertion mutations throughout the ure gene cluster and determined the effect of these mutations on production and regulation of urease activity in Escherichia coli. Mutations were obtained, with locations determine by DNA sequencing, in all genes except ureA and ureE. In each case, the mutation resulted in a urease-negative phenotype.